Estudo geofísico em aterro controlado disposto sobre rochas fraturadas - Moreira, César Augusto [UNESP]; Oliveira, Monica Teixeira de; Silva, Ariveltom Cosme da (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2011)
Geophysical survey is an important method for investigation of contaminated areas used in the characterization of contrasting physical properties in the presence of pollutants. This work applied the geophysical methods of Electrical Resistivity and Self Potential in waste landfill, located in Caçapava do Sul city, RS. The landfill is located over fractured metamorphic rocks. Eight lines of electrical profiling with 288 measures of self potential were done. In addition, 83 measurements of direction and dip of fractures were taken. The application of spontaneous potential method permitted to detect the direction of groundwater flow. The electrical resistivity measurements allowed the identification of low-intensity anomalies associated with the presence of leachate. There is a relationship between anomalous zones and the directions of fractures.

A geofísica é uma importante ferramenta de investigação de áreas contaminadas, utilizada na caracterização de contrastes de propriedades físicas no ambiente geológico na presença de substâncias poluentes. Este trabalho aplica os métodos geofísicos da Eletrorresistividade e do Potencial Espontâneo numa área de disposição de resíduos sólidos desativada, localizada no município de Caçapava do Sul, RS. O aterro está assentado sobre rochas metamórficas fraturadas. Foram realizadas 8 linhas de caminhamento elétrico e 288 medidas de potencial elétrico natural. Também foram realizadas 83 medidas de direção e sentido de fraturas. A aplicação do método do potencial espontâneo permitiu detectar o sentido do fluxo d’água subterrâneo. As medidas de resistividade elétrica permitiram identificar anomalias de baixa intensidade associadas à presença de chorume. Houve uma relação entre zonas anômalas com as direções de fraturas.
Geophysical study in waste landfill localized above fractured rocks
Keywords: Geophysics; Electrical resistivity; Voltage; Leachate; Fractures; Geofísica; Resistividade elétrica; Voltagem; Chorume; Fraturas